Factors involved in resilience: Siblings of adolescents in conflict with the law - Monjarás Rodríguez, María T. (2022)
To identify protective factors, in order to prevent adolescents from engaging in behaviors in conflict with the law, is very important to reduce costs on personal and public levels. The purpose of the present study is to explore the presence of resilient indicators among the siblings of adolescents in conflict with the law and to describe the factors involved in the presence of these indicators. Also to know the differences between both groups with the purpose to describe those possible protective factors that allow adolescents at risk, not to engage in criminal conduct, despite being immersed in adverse situations similar to those of their siblings in conflict with the law. For this purpose, a mixed study was conducted with 10 adolescents (5 in conflict with the law and 5 siblings without conflict), finding that the main protective factors in siblings are external or internal support of the family, continuing their studies and neutralizing stressful events.